IL7R gene expression network associates with human healthy ageing. Issue 1 (December 2015) - Passtoors, Willemijn; van den Akker, Erik; Deelen, Joris; Maier, Andrea; van der Breggen, Ruud; Jansen, Rick; Trompet, Stella; van Heemst, Diana; Derhovanessian, Evelyna; Pawelec, Graham; van Ommen, Gert-Jan; Slagboom, P.; et al.
Abstract Background The level of expression of the interleukin 7 receptor (IL7R ) gene in blood has recently been found to be associated with familial longevity and healthy ageing. IL7R is crucial for T cell development and important for immune competence. To further investigate the IL7R pathway in ageing, we identified the closest interacting genes to construct anIL7R gene network that consisted ofIL7R and six interacting genes:IL2RG, IL7, TSLP, CRLF2, JAK1 andJAK3 . This network was explored for association with chronological age, familial longevity and immune-related diseases (type 2 diabetes, chronic obstructive pulmonary disease and rheumatoid arthritis) in 87 nonagenarians, 337 of their middle-aged offspring and 321 middle-aged controls from the Leiden Longevity Study (LLS). Results We observed that expression levels within theIL7R gene network were significantly different between the nonagenarians and middle-aged controls (P = 4.6 × 10−4 ), being driven by significantly lower levels of expression in the elderly ofIL7, IL2RG andIL7R . After adjustment for multiple testing and white blood cell composition and in comparison with similarly aged controls, middle-aged offspring of nonagenarian siblings exhibit a lower expression level ofIL7R only (P = 0.006). HigherIL7R gene expression in the combined group of middle-aged offspring and controls is associated with a higher prevalence of immune-related disease (P = 0.001). On the one hand, our results indicate that lowerIL7R expression levels, as exhibited by the members of long-lived families that can be considered as 'healthy agers', are beneficial in middle age. This is augmented by the observation that higherIL7R gene expression associates with immune-related disease. On the other hand, IL7R gene expression in blood is lower in older individuals, indicating that lowIL7R gene expression might associate with reduced health. Interestingly, this contradictory result is supported by the observation that a higherIL7R gene expression level is associated with better prospective survival, both in the nonagenarians (Hazard ratio (HR) = 0.63, P = 0.037) and the middle-aged individuals (HR = 0.33, P = 1.9 × 10–4 ). Conclusions Overall, we conclude that the IL7R network reflected by gene expression levels in blood may be involved in the rate of ageing and health status of elderly individuals.